Distinctive Reproductive Phenotypes in Peripubertal Girls at Risk for Polycystic Ovary Syndrome - Torchen, Laura C (J Clin Endocrinol Metab, 2019)
CONTEXT: Increased testosterone (T) levels are a cardinal feature of polycystic ovary syndrome (PCOS). Female relatives of affected women, including premenarchal daughters, have elevated T levels supporting a genetic susceptibility to this phenotype. Girls with obesity (OB-g) also have increased T levels throughout puberty, which may indicate risk for PCOS. OBJECTIVE: We tested the hypothesis that premenarchal daughters of women affected with PCOS (PCOS-d) have distinctive phenotypic features compared with OB-g. DESIGN, SETTING, AND PARTICIPANTS: Forty-eight PCOS-d, 30 OB-g, and 22 normal weight (NW-g) premenarchal girls were studied. Mothers of OB-g and NW-g had no evidence for PCOS. MAIN OUTCOME MEASURES: Reproductive hormones were measured. RESULTS: Body mass index differed by design, was highest in OB-g, followed by PCOS-d (P > 0.001). PCOS-d and OB-g had similar increases in free T levels compared with NW-g (PCOS-d vs NW-g, P = 0.01; OB-g vs NW-g, P = 0.0001). Sex hormone binding globulin levels were lowest in OB-g and lower in PCOS-d than in NW-g (PCOS-d vs NW-g, P = 0.005; OB-g vs NW-g, P < 0.0001; PCOS-d vs OB-g, P < 0.0001). Anti-Müllerian hormone (AMH) levels in PCOS-d were significantly increased compared with OB-g, who tended to have lower AMH levels than NW-g (PCOS-d vs OB-g, P < 0.0001; PCOS-d vs NW-g, P = 0.10). CONCLUSIONS: Despite similarly elevated free T levels, PCOS-d had increased AMH levels compared with OB-g. This finding suggests that OB-g lack alterations in ovarian folliculogenesis, a key reproductive feature of PCOS. Causal mechanisms may differ in PCOS-d or OB-g, or elevated T in OB-g may not be an early marker for PCOS.